2016
DOI: 10.1111/luts.12150
|View full text |Cite
|
Sign up to set email alerts
|

Serum Testosterone Levels Are Negatively Correlated with International Prostate Symptom Score and Transitional Prostate Volume

Abstract: As total testosterone levels decrease, both International Prostate Symptom Score and transitional prostate volume increase significantly. These findings provide evidence of the presence of more severe lower urinary tract symptoms and larger transitional prostate volume in aging men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
10
2
Order By: Relevance
“…1 In the present study, although the authors stated that the patients in both groups have a normal pituitary-gonadal axis, the testosterone levels of the patients were not mentioned. The authors demonstrated the important role of the nervous system in the development of benign prostate hyperplasia (BPH).…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…1 In the present study, although the authors stated that the patients in both groups have a normal pituitary-gonadal axis, the testosterone levels of the patients were not mentioned. The authors demonstrated the important role of the nervous system in the development of benign prostate hyperplasia (BPH).…”
contrasting
confidence: 52%
“…Shim et al reported that total testosterone levels showed a significant negative correlation with transitional prostate volume in their study. 1 In the present study, although the authors stated that the patients in both groups have a normal pituitary-gonadal axis, the testosterone levels of the patients were not mentioned. If the testosterone levels were presented, the study would be more significant.…”
contrasting
confidence: 52%
“…The most common cause of LUTS in men is prostate enlargement and progression of BPH. A number of studies have suggested that an inverse association exist between serum T levels and LUTS; however, the underlying biochemical and physiological mechanisms by which reduced T levels affect LUTS have yet to be fully delineated [70717273]. A significantly larger prostate volume was reported in men afflicted with Met S [1921747576], however it is unclear if this increase in prostate volume indeed exerts a clinical significance [32].…”
Section: Metabolic Syndrome Testosterone Deficiency and Pathophysiomentioning
confidence: 99%
“…Within the published literature, male hypogonadism and its related comorbidities appear associated with poor clinical outcomes, [19][20][21][22][23] increased economic burden on healthcare systems, [24][25][26] and burdensome patient-reported symptoms. [27][28][29] Specific to comorbidities, limited data were available on the burden of obesity and T2DM in patients with male hypogonadism, which may be associated with the close link between these diseases.…”
Section: Burden Of Male Hypogonadism and Related Comorbiditiesmentioning
confidence: 99%
“…In addition to its overall clinical and economic burden, male hypogonadism is also associated with negative impacts on individual patients' experiences, through burdensome patient-reported symptoms, 27,28 and reduced quality of life. 29 In a prospective study of men in Taiwan (n=680), risk of erectile dysfunction (defined as scoring ≤7 on the International Index of Erectile Function) was significantly increased in men with low testosterone: ×2.4 with total testosterone <11 nmol/L, and ×3.0 with free testosterone <0.23 nmol/L (p<0.05).…”
Section: Burdensome Patient-reported Symptomsmentioning
confidence: 99%